Fracture Resistance of Lithium Disilicate, Indirect Resin Composite and Zirconia By Using Dual Cure Resin Cements - KAHRAMANOĞLU, ERKUT (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: The aim of the study was to examine the fracture resistance of lithium disilicate, indirect resin composite and zirconia by using dual cure resin cements. Methods: Three groups of 180 samples (n= 60) of E-max, zirconia and indirect resin composite materials (10mm diameter and 1 mm thickness). Discs were fabricated and cemented with three dual curing resin cements. Aging treatment was then applied to the discs by using thermal cycle machine (at 5 degrees C to 55 degrees C/dwell time: 20s), 10000 cycles for 168 hours' 7 days. Fracture tests were performed to the sample discs using piston on three balls test to determine the biaxial flexure strength of the 180 discs of the three materials. The results were analysed by using one-way analysis of variance (ANOVA) and t-test. Results: Statistically significant difference was found between control groups (before cementation and thermal cycle) and both group B (after cementation before thermal cycle) and group C (after cementation and thermal cycle) in all materials (P<0.05). Comparing Zirconia, Gradia and E-max all control groups showed statistically significant difference and Zirconia was showed greater flexural resistance against other materials. In addition, all materials also showed statistically significant difference in Variolink/Multilink cemented Group B and C. In Nexus cemented Group B and C statistically significant difference was found only Zirconia material. Similar to control group results, Zirconia material was showed greater flexural resistance values with both cements in Group B and C. Conclusion: There is a difference between flexural strength of the three materials, Zirconia has a better flexural strength when compared to lithium disilicate and indirect resin composite.
Keywords: Zirconia; lithium disilicate; indirect resin composite; fracture resistance; thermal cycle; FLEXURAL STRENGTH; TOUGHNESS; SURFACE; THICKNESS; STABILITY; HARDNESS; SHADE; COLOR